Mercosur – a Comparison of Four Member Countries on the Basis of Selected Economic Indicators - Hinčica, Vít; Mizerová, Michala; Řezanková, Hana (Comparative Economic Research. Central and Eastern Europe, 2020)
The aim of this paper is to present how countries can be compared on the basis of the development of selected macroeconomic indicators. The economic similarity of the four founding Mercosur countries (i.e., Argentina, Brazil, Paraguay, and Uruguay), based on the development of five selected macroeconomic indicators in the period 1991–2016, is investigated. The following indicators were analyzed: current account balance, GDP per capita, trade-to-GDP ratio, unemployment rate, and the GDP deflator, using data from the World Bank database. Using hierarchical cluster analysis of changes in time series (differences and growth rates), it was found that the obtained clusters of countries are different. For this reason, cluster analysis was carried out for two different groups of indicators on the basis of the averages of the Euclidean distances obtained for the individual indicators.